Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3389/fnbeh.2014.00426
|View full text |Cite
|
Sign up to set email alerts
|

Forced-choice decision-making in modified trolley dilemma situations: a virtual reality and eye tracking study

Abstract: Based on the frameworks of dual-process theories, we examined the interplay between intuitive and controlled cognitive processes related to moral and social judgments. In a virtual reality (VR) setting we performed an experiment investigating the progression from fast, automatic decisions towards more controlled decisions over multiple trials in the context of a sacrificing scenario. We repeatedly exposed participants to a modified ten-to-one version and to three one-to-one versions of the trolley dilemma in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 53 publications
4
66
2
4
Order By: Relevance
“…Mikhail, 2007;Thomson, 1976Thomson, , 1985Unger, 1996). So far, research on modified trolley dilemmas has shown that people in general act utilitarian and are relatively comfortable with utilitarian ADVs, programmed to minimize harm (Bonnefon et al, 2016;Skulmowski, Bunge, Kaspar, & Pipa, 2014). In contrast, German law interdicts the evaluation of human life (Art.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mikhail, 2007;Thomson, 1976Thomson, , 1985Unger, 1996). So far, research on modified trolley dilemmas has shown that people in general act utilitarian and are relatively comfortable with utilitarian ADVs, programmed to minimize harm (Bonnefon et al, 2016;Skulmowski, Bunge, Kaspar, & Pipa, 2014). In contrast, German law interdicts the evaluation of human life (Art.…”
Section: Introductionmentioning
confidence: 99%
“…This way of presenting the dilemma introduces issues like the disregard of important contextual and situational influences in moral decision-making (Skulmowski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This illustrates what VR is useful for in these types of context. Finally, Skulmowski et al (2014) used a screen-based system to situate participants in a trolley that they could control and avoid colliding with people standing on branching tracks. They investigated a number of hypotheses relating to specific types of potential victims (male, female), the number balanced against each other (e.g., 10 people rather than 5 against 1, or 1 against 1), ethnicity, altogether with 11 different hypotheses.…”
Section: Virtual Representations Of Moral Dilemmasmentioning
confidence: 99%
“…Recently, advances in virtual reality (VR) technologies have allowed the investigation of simulated moral actions in behavioural paradigms (e.g., Francis et al, 2016Francis et al, , 2017Patil, Cogoni, Zangrando, Chittaro, & Silani, 2014). Although these novel approaches have revealed mixed findings (Navarrete, McDonald, Mott, & Asher, 2012;Skulmowski, Bunge, Kaspar, & Pipa, 2014), recent virtual paradigms have found an increased preference for utilitarian actions in VR, when compared to text-based judgements. This has been observed in impersonal (i.e., switch dilemma; Pan & Slater, 2011;Patil et al, 2014) and personal moral dilemmas (i.e., footbridge dilemma; Francis et al, 2016Francis et al, , 2017McDonald, Defever, & Navarrete, 2017).…”
mentioning
confidence: 99%